Clinical case of manifestation of tuberous sclerosis in a child - Yu.A. Chornyi; I.H. Samoilenko; Yu.S. Tolmachova; O.O. Dziuba; V.A. Bilanenko (Zaslavsky O.Yu., 2021)
We have provided information about prevalence, etiology and pathogenesis of the tuberous sclerosis complex, a rare hereditary disease, caused by genetic mutation in TSC1 and TSC2 genes. Clinical and morphological manifestations of the disease were considered, according to updated diagnostic criteria, approved by the 2012 International Tuberous Sclerosis Complex Consensus Conference, as well as management of patients and prognosis were briefly described. Given that tuberous sclerosis is a rare disease with a polymorphic clinical picture (may affect the skin, central nervous system, kidneys, cardiovascular system, other organs and systems) and the manifestation at different times, and taking into account a low awareness of primary care physicians (especially pediatricians, who are more likely to face a child with the first signs of tuberous sclerosis) and specialist physicians, the correct diagnosis may often require years from the emergence of the first symptoms and lead to a deterioration in the health of patients and reducing the overall quality of life due to the development of complications that could be avoided. Our own clinical observation was performed of the tuberous sclerosis complex in a girl, who was treated in the MNPE "Children's Regional Hospital" at Kirovohrad Regional Council, with a detailed description of the course of the disease, starting before the patient's birth when the first symptoms were suspected during ultrasound screening, as well as the child's current state; we have also presented the results of additional instrumental researches. Given that the disease in the girl was suspected before her birth, establishing the correct diagnosis did not require a lot of time, but not in all patients the disease manifests so early, therefore, it is important to preserve the alertness regarding tuberous sclerosis complex and other hereditary diseases.